Analysis of College Classes Based on U-CLASS System Using Personal Mobile Nodes. (24th May 2015) - Kim, Chonggun; Kim, Jeongmi; Park, Hohwan; Ha, Ilkyu
The increase in mobile communications has led to advanced educational methods and technologies through accepting new technologies. A lot of studies have tried to overcome temporal and spatial limits on using personal mobile devices and have tried to increase learning effectiveness using various efficient educational methods. In this paper, U-CLASS, an interactive learning management system that provides interactive communications between a professor and students, is proposed and implemented. Monitoring of academic achievement after a real experiment with the proposed system and analysis of educational activities during the experimental class are important points. In order to achieve that, the proposed system was used in a practical class at a university, and educational activities from the classroom were gathered and analyzed. The data on the educational activities include frequency of questions, attendance rate, and seat positions of the students. Analysis results show that the average distance between professor and student in the classroom is strongly related to the grade of the student. Students who have a higher attendance rate and who ask more questions commonly show higher achievement.